Can artificial intelligence revolutionize soccer tactical analysis? - Plakias, S.; Kokkotis, C.; Giakas, G.; Tsaopoulos, D.; Moustakidis, S. (Trends in Sport Sciences, 2024)
Introduction. Adopting appropriate tactics and strategies is crucial for soccer teams aiming for victory. Soccer is undergoing a transformative renaissance with an infusion of artificial intelligence (AI), propelling a domain of tactical analysis into uncharted territories. Aim of Study. This narrative review seeks to provide a thorough overview of methodologies, challenges, and potential of AI in soccer tactical analysis. By collating current research, it aims to underscore AI`s transformative impact on soccer analysis, contributing fresh perspectives on tactical aspects. Material and Methods. A search was conducted in the Scopus, Web of Science, and EBSCO databases on August 29th, 2023, using a BOOLEAN expression to identify research articles in English on AI applications in soccer tactics. Results. From an initial pool of 90 articles, 23 were selected for review after screening for relevance and application of AI techniques in soccer tactics. These studies showcase AI`s diverse applications, from predictive analytics and real-time adjustments to pattern recognition and strategic planning. Conclusions. The integration of AI into soccer tactical analysis marks the beginning of a new era characterized by data-driven strategies and performance optimization. Through advanced machine learning (ML) models, neural networks, and complex algorithms, AI facilitates deeper, actionable insights into game dynamics and opponent strategies. This review enriches a scientific discourse by detailing AI`s pivotal role in modern soccer tactics, suggesting a future in which AI`s potential is fully harnessed, signifying a milestone in soccer`s analytical evolution.